Adaptasi Teknologi Informasi dan Komunikasi: Upaya Peningkatan Kapasitas Pegawai di Lingkungan Perguruan Tinggi - Buntari Buntari (Journal of Social and Political Science)
This article discusses adaptation carried out to keep abreast of information and communication technology (ICT). The need to accelerate the flow of information intended as an effort to create an effective, efficient and transparent bureaucracy is an urgent need. In this context, it is urged to discuss how a bureaucratic system that is arranged vertically and divided into basic tasks and work functions, is conditioned to enter a new system that employs ICT. Where the tendency that occurs is the presence of employees who are still reluctant to leave the comfort zone and prioritize carrying out their work according to their habits. On the other hand, the emergence of new employees who are able to adapt and develop ICT-based competencies. These two groups are important to map and discuss as a way to reflect the existence of a work system that can improve employee capacity.Keywords: Adaptation, Bureaucracy, Capacity Development, ICT